On Logic and Legislation. Some Philosophical Remarks: Array - Munteanu, Cristinel (Acta Universitatis Danubius. Juridica, 2020)
Starting from the conception of the ancient Greeks, which left deep marks in the Western culture, I tried to comment in this study on the relation between cosmology, logic and legislation. I was mainly interested in the connection between “natural law” and “social law” in general, but mostly in the relation between the former and the principles of “Roman law”. Apart from the philosophical aspects dealt with in this article, I have also presented some elements (connected to “repeated discourse”) which I analyzed from a linguistic point of view as well.